h+4=-3

Simple and best practice solution for h+4=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h+4=-3 equation:


Simplifying
h + 4 = -3

Reorder the terms:
4 + h = -3

Solving
4 + h = -3

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + h = -3 + -4

Combine like terms: 4 + -4 = 0
0 + h = -3 + -4
h = -3 + -4

Combine like terms: -3 + -4 = -7
h = -7

Simplifying
h = -7

See similar equations:

| -4(3y-6)-y=-3(y-4) | | 2x^2-22x+28.5=0 | | 16+z=14 | | (x^2)-2x-35=0 | | 4*(x*4)=32 | | 5n-2m=8 | | -2x^2+7x+1=17 | | 6x+8+7x-5=180 | | -p+7=5-(9p+4) | | -3r=42 | | 3x+24=8+7x | | 2.5x+(12-x)5.75=56 | | 4x-3(16x^2-24x+9)=0 | | 160=2*8*x | | -4m+-8m-30=90 | | -4x+3+6x-5=-14 | | 160=2*8x | | 2y+7=-3y+13 | | 3=2x+8 | | -16m+39=15m+17 | | -9m+5=-6 | | 2x+y-5=a | | 0.6=0.15x | | 5(t+1)=0 | | -2(d+6)=-18 | | 2x-39=61 | | 9x+2=12x-4 | | (5+6i)-(7-8i)= | | -1x-3=-2 | | 16/p=-4 | | 3x/2+6x+45=180 | | -3+7=8+2x |

Equations solver categories